Poetry and courtliness in Renaissance England - Javitch, Daniel (Princeton University Press, 1978)
Model court conduct in the Renaissance shared many rhetorical features with poetry. Analyzing these stylistic affinities, Professor Javitch shows that the rise of the courtly ideal enhanced the status of poetic art. He suggests a new explanation for the fostering of poetic talents by courtly establishments and proposes that the court stimulated these talents more decisively than the Renaissance school. The author focuses on late Tudor England and considers how Queen Elizabeth's court helped poetry gain strength by subscribing to a code of behavior as artificial as that prescribed by Castiglione. Elizabethan writers, however, could benefit from the court's example only so long as their contemporaries continued to respect its social and moral authority. The author shows how the weakening of the courtly ideal led eventually to the poet's emergence as the maker of manners, a role first subtly indicated by Spenser in the Sixth Book of The Faerie Queene.Originally published in 1978.The Princeton Legacy Library uses the latest print-on-demand technology to again make available previously out-of-print books from the distinguished backlist of Princeton University Press. These editions preserve the original texts of these important books while presenting them in durable paperback and hardcover editions. The goal of the Princeton Legacy Library is to vastly increase access to the rich scholarly heritage found in the thousands of books published by Princeton University Press since its founding in 1905.
Includes index.
Keywords: English poetry -- Early modern, 1500-1700 -- History and criticism.; Literature and society -- England -- History -- 16th century.; Renaissance -- England.; Great Britain -- Court and courtiers -- History -- 16th century.; Littérature et société -- Angleterre -- Histoire -- 16e siècle.; Renaissance -- Angleterre.; LITERARY CRITICISM -- Renaissance.; POETRY -- English, Irish, Scottish, Welsh.; Courts and courtiers; English poetry -- Early modern; Literature and society; Renaissance; England; Great Britain; 1500-1700; Criticism, interpretation, etc.; History